Differences in Mean Platelet Volume and Platelet Count between Children with Simple and Complex Febrile Seizures - NIKKHAH, Ali; SALEHIOMRAN, Mohammad Reza; ASEFI, Samane (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Nikkhah A, Salehiomran MR, Asefi SS. Differences in Mean Platelet Volume and Platelet Count between Children with Simple and Complex Febrile Seizures. Iran J Child Neurol. Spring 2017; 11(2):44-47. Abstract Objective The aim of our study was to find the relationship of MPV (Mean Platelet Volume) levels and platelet counts as markers of inflammation between simple and complex febrile seizures. Materials & Methods In this retrospective comparative study, we investigated the recordings of 356 children between 5 months and 6 yr with diagnosis of simple and complex febrile seizure (SFS&CFS) in Amircola’s Children’s Hospital, Babol University of Medical Sciences, Babol, Iran between Mar 2011 and Dec 2015. Results Mean age was similar in two groups. The MPV of the CFS group (8.32±0.48fl) was lower than that of the SFS group (8.58±0.34fl) but this difference was not significant statistically. The platelet count of the CFS group (315.03×103 ±117.17×103) was higher than that of SFS group (291.82×103 ± 87.49×103) but there was no significant statistical difference. Conclusion We did not find significant differences between two groups. Therefore, further studies about this idea should be performed. References 1. Commission on Epidemiology and Prognosis, International League Against Epilepsy. Guidelines for epidemiologic studies on epilepsy. Epilepsia 1993; 34:592–596. 2. Shinnar S. Febrile seizure. In: Swaiman KF, Ashwal S, Ferriero DM, editors. Pediatric neurology principle & practice. 4th ed, vol. 1.Philadelphia: Lippincott Williams & Wilkins Press; 2006. P. 1079-1089. 3. Shinnar S, Glauser TA. Febrile seizures. In: Pellock JM, Bourgeois FD, Edwin Dodson W. editors. Pediatric 47 epilepsy, Diagnosis & Therapy. 3rd ed. New York: Demos Press; 2008. P. 293- 301. Shinnar S, Glauser TA. Febrile seizures. J Child Neurol 2002; 17(suppl1):S44-S52. 4. Lux AL. Treatment of febrile seizures: historical perspective, current opinions, and potential future directions. Brain Dev 2010; 32(1):42-50. 5. Jons T, Jacobsen S.J. Childhood Febrile Seizures: Overview and Implications. Int J Med Sci 2007; 4(2):110- 4. 6. Iwasaki N, Nakayama J, Hamano K, et al. Molecular genetics of febrile seizures. Symposium I Epilepsia 2002; 43(9): 32-5. 7. Amirsalari S, Keihani doust Z, Ahmadi M, et al. Relationship between iron deficiency anemia and febrile seizures. Iran J Child Neurol 2010; (4)1:27-30. 8. Ghasemi F, Valizadeh F, Taee N. Iron-deficiency Anemia in Children with Febrile Seizures. A Case-Control Study. Iran J Child Neurol 2014; (8) 2:38-44. 9. Bidabadi E, Mashouf M. Association between iron deficiency anemia and first febrile convulsion: a case-control study. Seizure 2009; 18: 347-51. 10. Hartfield DS, Tan J, Yager JY, et al. The association between iron deficiency and febrile seizures in childhood. Clin Pediatr 2009; 48(4): 420-6. 11. Ozaydin E, Arhan E, Cetinkaya B, et al. Differences in iron deficiency anemia and mean platelet volume between children with simple and complex febrile seizures. Seizure 2012; 21(3): 211-214. 12. Weyrich AS. Platelets: more than a sack of glue. American Society of Hematology (ASH). Hematology 2014; 5(1):400-3. 13. Rondina MT, Weyrich AS, Zimmerman GA. Platelets as cellular effectors of inflammation in vascular diseases. Circ Res 2013; 112(11):1506-1519. 14. Semple JW, Italiano JE Jr, Freedman J. Platelet and the immune continuum. Nat Rev Immunol 2011; 11(4):264- 274. 15. Mahmut Abuhandan, Abdullah Solmaz, et al. Evaluation of Selenium Levels and Mean Platelet Volume in Patients with Simple Febrile Convulsion. Iran J Pediatr 2014; 24(4):401-405.